European bat lyssaviruses: Distribution, prevalence and implications for conservation - Harris, S.L. (Biol Conserv, 2006)
Worldwide, there are more than 1100 species of the Order Chiroptera, 45 of which are present in Europe, and 16 in the UK. Bats are reservoirs of, or can be infected by, several viral diseases, including rabies virus strains (in the Lyssavirus genus). Within this genus are bat variants that have been recorded in Europe; European bat lyssavirus 1 (EBLV-1), European bat lyssavirus 2 (EBLV-2) and, four currently unclassified isolates. Since 1977, 783 cases of EBLVs (by isolation of viral RNA) have been recorded in Europe. EBLV-1 or EBLV-2 has been identified in 12 bat species, with over 95% of EBLV-1 infections identified in Eptesicus serotinus. EBLV-2 is associated with Myotis species (Myotis daubentonii and Myotis dasycneme). A programme of passive surveillance in the United Kingdom between 1987 and 2004 tested 4871 bats for lyssaviruses. Of these, four M. daubentonii (3.57% of submitted M. daubentonii) were positive for EBLV-2. Potential bias in the passive surveillance includes possible over-representation of synanthropic species and regional biases caused by varying bat submission numbers from different parts of the UK. In 2003, active surveillance in the UK began, and has detected an antibody prevalence level of 1–5% of EBLV-2 in M. daubentonii (n = 350), and one bat with antibodies to EBLV-1 in E. serotinus (n = 52). No cases of live lyssavirus infection or lyssavirus viral RNA have been detected through active surveillance. Further research and monitoring regarding prevalence, transmission, pathogenesis and immunity is required to ensure that integrated bat conservation continues throughout Europe, whilst enabling informed policy decision regarding both human and wildlife health issues.